Laser induced spherical bubble dynamics in partially confined geometry with acoustic feedback from container walls - Lei Fu; Xiao-Xuan Liang; Sijia Wang; Siqi Wang; Ping Wang; Zhenxi Zhang; Jing Wang; Alfred Vogel; Cuiping Yao (Ultrasonics Sonochemistry, 2023)
We investigated laser-induced cavitation dynamics in a small container with elastic thin walls and free or partially confined surface both experimentally and by numerical investigations. The cuvette was only 8–25 times larger than the bubble in its center. The liquid surface was either free, or two thirds were confined by a piston-shaped pressure transducer. Different degrees of confinement were realized by filling the liquid up to the transducer surface or to the top of the cuvette. For reference, some experiments were performed in free liquid. We recorded the bubble dynamics simultaneously by high-speed photography, acoustic measurements, and detection of probe beam scattering. Simultaneous single-shot recording of radius-time curves and oscillation times enabled to perform detailed investigations of the bubble dynamics as a function of bubble size, acoustic feedback from the elastic walls, and degree of surface confinement. The bubble dynamics was numerically simulated using a Rayleigh-Plesset model extended by terms describing the acoustically mediated feedback from the bubble’s environment.Bubble oscillations were approximately spherical as long as no secondary cavitation by tensile stress occurred. Bubble expansion was always similar to the dynamics in free liquid, and the environment influenced mainly the collapse phase and subsequent oscillations. For large bubbles, strong confinement led to a slight reduction of maximum bubble size and to a pronounced reduction of the oscillation time, and both effects increased with bubble size. The joint action of breakdown-induced shock wave and bubble expansion excites cuvette wall vibrations, which produce alternating pressure waves that are focused onto the bubble. This results in a prolongation of the collapse phase and an enlargement of the second oscillation, or in time-delayed re-oscillations. The details of the bubble dynamics depend in a complex manner on the degree of surface confinement and on bubble size. Numerical simulations of the first bubble oscillation agreed well with experimental data. They suggest that the alternating rarefaction/compression waves from breakdown-induced wall vibrations cause a prolongation of the first oscillation. By contrast, liquid mass movement in the cuvette corners result in wall vibrations causing late re-oscillations. The strong and rich interaction between the bubble and its surroundings may be relevant for a variety of applications such as intraluminal laser surgery and laser-induced cavitation in microfluidics.